Deportation, memory and the self in Dalia Grinkevičiūtė’s memoirs A Stolen Youth, A Stolen Homeland and Lithuanians by the Laptev sea. - Raškauskienė, Audronė (European Journal of Life Writing, 2014)
The article addresses the issue of deportation, displacement, and the self in Dalia Grinkevičiūtė’s Lietuviai prie Laptevų jūros: Atsiminimai, miniatiūros, laiškai, written in 1949–50, first published in 1997, in 2002 translated as A Stolen Youth, a Stolen Homeland and in the second version of the memoirs, Lietuviai prie Laptevų jūros, written in 1974, in 1990 translated as Lithuanians by the Laptev Sea. During the mass deportations of 1941, Dalia Grinkevičiūtė (1927-1987) was deported from Lithuania to Siberia and spent almost 10 years in Yakut Republic. Considering Grinkevičiūtė’s life experience, writing memoirs may be understood as a means of composing or re-creating the self and looked at from the perspective of the narrative therapy.